Social Moral Approach in Reducing Corruption Rates - Mashudi, Mashudi (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
AbstractCorruption in Indonesia remains a significant issue that threatens social and economic stability across both the central and regional government sectors. Despite various legal efforts, including increased penalties for corruption offenders, this practice continues to thrive. This study aims to explore the impact of a social-moral approach on reducing corruption rates in Indonesia by combining legal sanctions with religiously based social-moral movements. The research utilizes a consilience approach, integrating environmental policy, ethics, and social sciences with the principles of maqashid al-syariah. The findings suggest that the